The Effect Of Menstruation On The Results Of Javelin Students Of Physical Education Bengkulu University - Septian Raibowo; Andes Permadi; Andika Prabowo; Oddie Barnanda Rizky; Bogy Restu Ilahi (Hanoman Journal: Physical Education and Sport, 2023)
This study aims to determine the effect of menstruation on the results of javelin the students of physical education study program of Bengkulu university. This study uses quantitative method with pre-eksperimental design. The population of this study were all the students of physical education study program of Bengkulu University, totaling 88 people and the sample is 30 people using purposive sampling technique. The instrument used is a test using javelin test. The study conducted on the result of javelin when not menstruating and when menstruating are the same. The test result show that there is the effect of menstruation on the result of javelin. The effect test obtained t count 13.7 and t table 1.699 so that it shows ho is rejected and Ha is accepted which means that there is the effect of menstruation on the result of javelin the student of physical education study program of Bengkulu University.